Detecting evolutionary forces in language change - Newberry, Mitchell G.; Ahern, Christopher A.; Clark, Robin; Plotkin, Joshua B. (Nature (London), 2017)
Analyses of digital corpora of annotated texts reveal the influence of stochastic drift versus selection in grammatical shifts in English and provide a general method for quantitatively testing theories of language change. Gauging language evolution Languages and genes are transmitted between generations, both being subject to change with each step through random fluctuation as well as natural selection. Joshua Plotkin and colleagues assess the contribution of these two evolutionary mechanisms in a large body of texts ranging from the 12th to the 21st centuries. Some of the findings, for example that rare words are more prone to random drift than common ones, are perhaps not surprising. However, selection for the irregular forms of some verbs tends to buck the usual assumption of regularization over time, and might be related to changing frequencies of rhyming patterns. The findings suggest a more important role for random processes in language evolution than previously considered. Both language and genes evolve by transmission over generations with opportunity for differential replication of forms 1 . The understanding that gene frequencies change at random by genetic drift, even in the absence of natural selection, was a seminal advance in evolutionary biology 2 . Stochastic drift must also occur in language as a result of randomness in how linguistic forms are copied between speakers 3 , 4 . Here we quantify the strength of selection relative to stochastic drift in language evolution. We use time series derived from large corpora of annotated texts dating from the 12th to 21st centuries to analyse three well-known grammatical changes in English: the regularization of past-tense verbs 5 , 6 , 7 , 8 , 9 , the introduction of the periphrastic ‘do’ 10 , and variation in verbal negation 11 . We reject stochastic drift in favour of selection in some cases but not in others. In particular, we infer selection towards the irregular forms of some past-tense verbs, which is likely driven by changing frequencies of rhyming patterns over time. We show that stochastic drift is stronger for rare words, which may explain why rare forms are more prone to replacement than common ones 6 , 9 , 12 . This work provides a method for testing selective theories of language change against a null model and reveals an underappreciated role for stochasticity in language evolution.